Genome-Wide Identification of CBL-CIPK Gene Family in Honeysuckle (Lonicera japonica Thunb.) and Their Regulated Expression Under Salt Stress - Huang, Luyao; Li, Zhuangzhuang; Fu, Qingxia; Liang, Conglian; Liu, Zhenhua; Liu, Qian; Pu, Gaobin; Li, Jia (Frontiers in Genetics, 2021)
In plants, calcineurin B-like proteins (CBLs) are a unique group of Ca2+ sensors that decode Ca2+ signals by activating a family of plant-specific protein kinases known as CBL-interacting protein kinases (CIPKs). CBL-CIPK gene families and their interacting complexes are involved in regulating plant responses to various environmental stimuli. To gain insight into the functional divergence of CBL-CIPK genes in honeysuckle, a total of six LjCBL and 17 LjCIPK genes were identified. The phylogenetic analysis along with the gene structure analysis divided both CBL and CBL-interacting protein kinase genes into four subgroups and validated by the distribution of conserved protein motifs. The 3-D structure prediction of proteins shown that most LjCBLs shared the same Protein Data Bank hit 1uhnA and most LjCIPKs shared the 6c9Da. Analysis of cis-acting elements and gene ontology implied that both LjCBL and LjCIPK genes could be involved in hormone signal responsiveness and stress adaptation. Protein-protein interaction prediction suggested that LjCBL4 is hypothesized to interact with LjCIPK7/9/15/16 and SOS1/NHX1. Gene expression analysis in response to salinity stress revealed that LjCBL2/4, LjCIPK1/15/17 under all treatments gradually increased over time until peak expression at 72 h. These results demonstrated the conservation of salt overly sensitive pathway genes in honeysuckle and a model of Ca2+-LjCBL4/LjSOS3-LjCIPK16/LjSOS2 module-mediated salt stress signaling in honeysuckle is proposed. This study provides insight into the characteristics of the CBL-CIPK gene families involved in honeysuckle salt stress responses, which could serve as a foundation for gene transformation technology, to obtain highly salt-tolerant medicinal plants in the context of the global reduction of cultivated land.